Perceptions of the impacts of urban sprawl among urban and peri-urban dwellers of Hyderabad, India: A latent class clustering analysis - Hatab, Assem Abu; Ravula, Padmaja; Nedumaran, Swamikannu; Lagerkvist, Carl Johan (Springer, 2022)
Like many other developing countries, urban sprawl is a growing phenomenon in India, which poses socio-economic and environmental challenges that worryingly affect urban sustainability. In this study, a latent class clustering approach was used to investigate perceptions of urban sprawl among 622 urban and peri-urban dwellers in Hyderabad. The empirical results clustered the respondents into three distinct classes based on their perceptions of urban sprawl impacts: ‘undecided respondents’, ‘negative perceivers’, and ‘opportunity perceivers’. The majority of respondents were undecided with no strong views towards the impacts of urban sprawl, which may increase their vulnerability and hinder effective adaptation to the adverse economic, social and environmental effects of urban sprawl. This also provokes concerns about the effectiveness of government interventions to build public awareness of urban development and its impacts on the city. With regard to the role of demographic and socio-economic characteristics in shaping the perception of the respondents, the results revealed that social caste plays a determining role in forming dwellers’ perception. In particular, members of marginalised social castes were more likely to form positive perceptions of the impacts of urban sprawl as urban expansion generates better and stable income that improve their social status. In addition, individuals with higher levels of education were more likely to form negative or positive perceptions, implying that efforts to raise social capital could be a useful means for mitigating the impacts of urban sprawl. Finally, membership in community development organisations was a key factor in dictating membership of the negative perceivers’ class. Overall, our findings suggest that an appropriate policy framework and specific programmes are needed for enhancing dwellers’ perception towards the impacts of urban sprawl, which can enhance the design, acceptance, and implementation of a more sustainable governance of urbanisation and contribute to achieving urban sustainability in developing countries.